Cultural Tourism and Architecture Heritage: Question of Authenticity - Riddhagni, Nethchanok (Journal of Community Development Research (Humanities and Social Sciences); Vol 11 No 3 (2561): July-September 2018, 2018)
Tourism industry is the largest industry that has grown dramatically fast. Sustaining cultural authenticity is essential within the field of cultural tourism, as the interest of tourists in travelling is closely related to natural as well as cultural heritage sites. Thus, it has led different destinations to focus on the authenticity and has significantly increased cultural tourism industry in such countries. The desire of tourists to get indulged in the culture of the other countries has made it essential for the tourism authorities to maintain and sustain the originality and authenticity of the cultural heritage.      This study radiates more light on the question of cultural and architectural heritage and authenticity. It has also been observed that cultural heritage resources are consistently offered as the central aspect for prompting the development of cultural tourism. The visitor’s consumption of the preferred experiences provided by cultural heritage attractions helps in increasing the cultural tourism. Travellers want the hotels to represent the local neighborhood, have a strong sense of place with local food, art and traditions. Therefore, restoring, preserving, keeping alive and managing historical buildings or making them look old and authentic could fulfill quest for authenticity in the accommodation market. Therefore, based on the study findings, it can be stated that the cultural factors are becoming more popular in Thailand. It has hence been marked that, with the drastically increasing number of tourists in Thailand over the years, the cultural tourism has taken the position as one of the most important segments of Thailand’s economy.      There are many possibilities for future research in this area. Authenticity is subjectivity of human beings. As beauty is in the eye of the beholder, what is real to one person can be very fake to another. Also there can be more factors that should take into consideration for measuring authenticity. Finally, the focus of the study was on heritage accommodation, there is a varied area in the tourism industry to be further studied. Keywords : Cultural, Architectural, Heritage, Authenticity, Sustainable Tourism